1966
DOI: 10.2337/diab.15.8.555
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Release of Insulin by an Extract of Intestinal Mucosa

Abstract: The mechanism of action of an extract of intestinal mucosa that accelerates the disposal of glucose given intravenously in normal man was investigated. The active material is biologically distinguishable from pancreozymin, and its effects cannot be attributed to insulin, insulin-like activity, glucagon or amino acids in the preparation. The extract enhances the increase in blood-insulin concentration which occurs in response to the intravenous infusion of glucose in normal man and which has been compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

1971
1971
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(24 citation statements)
references
References 0 publications
1
23
0
Order By: Relevance
“…Recently, these effects ofthe endocrine pancreas previously attributed to CCK have been ascribed to contaminating gastric inhibitory polypeptide (GIP) present in impure preparations of CCK (9,10). In fact, Dupr6 and Beck (11), and other investigators (12)(13)(14) found no such effects of the hormone when highly purified CCK was used. More recently, however, synthetic COOH-terminal octapeptide of CCK has been shown to stimulate the release of insulin and glucagon both in vivo (15) and in vitro (6, 7).…”
Section: Introductionmentioning
confidence: 96%
“…Recently, these effects ofthe endocrine pancreas previously attributed to CCK have been ascribed to contaminating gastric inhibitory polypeptide (GIP) present in impure preparations of CCK (9,10). In fact, Dupr6 and Beck (11), and other investigators (12)(13)(14) found no such effects of the hormone when highly purified CCK was used. More recently, however, synthetic COOH-terminal octapeptide of CCK has been shown to stimulate the release of insulin and glucagon both in vivo (15) and in vitro (6, 7).…”
Section: Introductionmentioning
confidence: 96%
“…Peptidergic signals derived from the intestine augment the insulin response induced by nutrients ("the incretin effect") (Dupre and Beck, 1966;Fehmann et al, 1995a). This functional connection between the intestine and the islets of Langerhans was termed the "incretin axis" or "entero-insular-axis" (Unger and Eisentraut, 1969;Fehmann et al, 1995a).…”
Section: The Glucagon-like Peptide-1 Receptormentioning
confidence: 99%
“…The mechanism behind this phenomenon, termed incretin [5], has received much attention, but its nature has not yet been entirely explained. The incretin effect has mainly been conceived as being of hormonal nature [6][7][8][9][10][11]. However, it might also be due to neural augmentation of the insulin response [4,[12][13][14], though until now no studies have excluded this possibility.…”
mentioning
confidence: 99%